Utilization of YouTube for Developing Communication Skills and Imagination in Preschool Children: A Parent's Perspective - Yuliastanti, Triani; Nurrahma, Herlin Ajeng; Siradz, Bayu Firdaus (Qualitative and Quantitative Research Center, 2024)
YouTube has become one of the most popular and frequently accessed platforms by parents to find various sources of learning and entertainment for their children. Developing communication and imagination skills in preschool children can open the door to creativity and problem-solving that will shape how they interact with the world. Parents must play an active role in forming a solid foundation for preschool children’s communication and imagination skills. This study aims to analyze parents’ perspectives on using YouTube on children’s imagination and communication skills. The research method uses the Structural Equation Model. The sample size for this study is 100 parents. The sampling technique used purposive sampling, using the criteria of parents with preschool-aged children and a habit of watching YouTube in Boyolali, Indonesia. The results showed that according to the parent’s perspective, preschool children’s habit of watching YouTube significantly influences their imagination and communication skills. The perspective of parents directly involved in preschool children’s learning process can be a revolutionary tool in shaping communication and imagination skills. Parents who are directly involved in their children’s learning process through YouTube have the power to create immersive and enjoyable learning experiences, bridging the gap between technology and the development of children’s communication skills and imagination in innovative and impactful ways. This research contributes to increasing the understanding of digital media integration in early childhood education and how parents can leverage technology to support the development of essential skills in children.